Note from the editor: Climate change, capitalism, and growth - Anita Engels (economic sociology_the european electronic newsletter, 2021)
Welcome to the third and last issue of this Newsletter on economic sociology and climate change. The past months have been very exciting for someone who is interested in the fate of the Paris climate goals. An increasing number of countries and companies have declared so-called net-zero emissions, carbon neutrality or climate neutrality targets by the year 2050, 2040, or even 2030. In addition, study after study tends to show how these goals can actually still be achieved, even though time is almost up. Among them is a report issued by the International Energy Agency in May 2021 which argued that the "world has a viable pathway to building a global energy sector with net-zero emissions in 2050" (IEA 2021) - an institution that seemed so far firmly rooted in the fossil fuel era. [...]
Keywords: 300